2000
DOI: 10.1007/s11746-000-0036-2
|View full text |Cite
|
Sign up to set email alerts
|

Frying performance of low‐linolenic acid soybean oil

Abstract: The frying performance of low-linolenic acid soybean oil from genetically modified soybeans was examined. Partially hydrogenated and unhydrogenated low-linolenic acid soybean oils were compared to two partially hydrogenated soybean frying oils. Frying experiments utilizing shoestring potatoes and fish nuggets were conducted. Frying oil performance was evaluated by measuring free fatty acid content, p-anisidine value, polar compound content, soap value, maximal foam height, polymeric material content, and Lovib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 14 publications
3
49
0
3
Order By: Relevance
“…Therefore, ultrasonic velocity is a parameter which allows assessing oil quality and oil stability. Indeed, previous studies indicated that a lower linoleic acid content in soybean oil resulted in improved oil quality during cooking and frying (Tompkins, 2000). In this study, changes in the fatty acid profile of oils during frying are basically among the unsaturated fatty acids, whereas the saturated fatty acids are slightly increased.…”
Section: Ultrasonic Measurementsmentioning
confidence: 49%
“…Therefore, ultrasonic velocity is a parameter which allows assessing oil quality and oil stability. Indeed, previous studies indicated that a lower linoleic acid content in soybean oil resulted in improved oil quality during cooking and frying (Tompkins, 2000). In this study, changes in the fatty acid profile of oils during frying are basically among the unsaturated fatty acids, whereas the saturated fatty acids are slightly increased.…”
Section: Ultrasonic Measurementsmentioning
confidence: 49%
“…Os ácidos graxos livres são moderadamente voláteis e uma quantidade desconhecida é perdida durante o aquecimento. Níveis moderados de ácidos graxos livres parecem não estar relacionados com a qualidade inferior do alimento e os ácidos graxos livres podem sofrer oxidação e serem convertidos em outros produtos que não são medidos por métodos de titulação (TOMPKINS & PERKINS, 2000).…”
Section: Resultsunclassified
“…This was consistent with findings from previous studies showing that the amounts of polymers increased with an increase in the number of fryings and the frying temperature. These polymers cause higher oil absorption of foods [17]. After third frying, the highest absorption of RBO+SO and the lowest absorption of RBO+GO in both ratios could be due to the presence of linoleic acid and oleic acid respectively.…”
Section: Discussionmentioning
confidence: 98%
“…After second frying absorption of all the blended oils (70: 30, 80:20) increased significantly (p≤0.05) whereas after third frying there was a significant (p≤0.05) decline in the absorption rate except in the RBO+SO in the both ratios. As the number of fryings and the frying temperature increase, the amounts of polymers increased [17]. Polymers cause higher oil absorption of foods and the oil rich in linoleic acid is more easily polymerized during deep-fat frying than the oil rich in oleic acid [18].…”
Section: Percent Fat Absorption Of Blended Oilsmentioning
confidence: 99%